Blood glucose levels and bodyweight change after dapagliflozin administration. Issue 9 (28th February 2021) - Kim, Hyunah; Lee, Seung‐Hwan; Lee, Hyunyong; Yim, Hyeon Woo; Cho, Jae‐Hyoung; Yoon, Kun‐Ho; Kim, Hun‐Sung
Abstract: Aims/Introduction: Increased blood glucose or increased weight is often observed in patients who are prescribed sodium–glucose cotransporter 2 inhibitors (SGLT2i). The aim of this study was to determine in advance which patients, among those prescribed a SGLT2i, would be likely to have improved or worsened blood glucose levels and gain or loss of weight through the use of real‐world data‐based prescriptions. Materials and Methods: After 3 months of dapagliflozin prescription, patients were divided into four groups: H(+)W(+) for improved glucose and weight loss; H(+)W(−) for improved blood glucose and weight gain; H(−)W(+) for worsened glucose and weight loss; and H(−)W(−) for worsened glucose and weight gain. Results: The proportion of patients in the H(+)W(+) group was 53.5% (325/608 patients), H(+)W(−) was 19.7% (120/608), H(−)W(+) was 26.8% (114/608) and H(−)W(−) was 8.1% (49/608). The odds of proceeding to H(+)W(−) compared with H(+)W(+), which served as the reference, were 144% in baseline hemoglobin A1c (HbA1c) 7.0–8.0%, 233% in baseline HbA1c 8.0–9.0% and 359% in baseline HbA1c ≥ 9.0% (odds ratio 3.59, P < 0.05) compared with the reference. The odds of proceeding to H(−)W(+) were 29, 13 and 8%, respectively (all P < 0.05), and to H(−)W(−) were 17, 15 and 8%, respectively (all P < 0.05), compared with the reference. The results were expected to vary individually, because changes in blood glucose and bodyweight are more affected by diet and exercise than by drugs. Conclusions: When first prescribing dapagliflozin, a physician should be aware of the weight gain rather than glucose change if the baseline HbA1c is high, and might concentrate on weight‐related lifestyle training, such as diet and exercise. Abstract : Increased blood glucose or increased weight is often observed in patients who are prescribed sodium–glucose cotransporter 2 inhibitors. Many other studies have shown that the glucose‐lowering effect seen in real‐world evidence studies is relatively low compared with that seen in conventional randomized controlled trials, even if the same drugs are used. When first prescribing dapagliflozin, a physician should be aware of the weight gain rather than glucose change if the baseline glycated hemoglobin is high, and might concentrate on weight‐related lifestyle training, such as diet and exercise.